Fe-doped MOF nanoparticles: the LIFR and BMP4 dual-signaling pathways activated regulator for in vitro expansion of mouse embryonic stem cells - Youyuan Li; Hong Wang; Zhilei Li; Huichao Wang; Yi Gao; Chaoran Wu; Bangguo Wei; Zhanyun Guo; Xijin Wang; Guoxin Jing; Shilong Wang (Materials Today Bio)
In the cultivation of mouse embryonic stem cells (mESCs), leukemia inhibitory factor (LIF) and mitotically inactive mouse embryonic fibroblasts (MEFs) are usually used to maintain the self-renewal and pluripotency of mESCs. However, the high cost of LIF and the immunogenicity of MEFs limit their clinical application in stable culture and large-scale expansion of mESCs. Therefore, it is necessary to pursue a low-cost, convenient, and safe alternative. This study found that Fe-doped metal organic framework nanoparticles (Fe MOF) have good biocompatibility under long-term cultivation and could maintain the self-renewal of mESCs in the absence of LIF and MEFs, without destroying the potential of mESCs to differentiate into three germ layer cells. Through transcriptome sequencing, it was demonstrated that Fe MOF nanomaterials could not only upregulate the expression of LIFR/GP130, but more importantly, they could activate the Fe3+ mediated BMP4/ALK/SMAD signaling pathway. The experimental results indicate that Fe MOF nanomaterials could effectively maintain the self-renewal and pluripotency of mESCs. This study demonstrates that Fe MOF could not only replace the LIF factor, but also has a stronger ability to promote the self-renewal of mESCs owe to its multi-signal pathway regulation function, providing application prospects in the in vitro cultivation of mESCs.